INTRODUCTION TO MATRICES AND LINEAR TRANSFORMATIONS - DANIEL T FINKBEINER (NEW YORK DOVER PUBLICATION, 1978)
A combination of formal theory and related computational techniques, it includes solutions to selected exercises.
Keywords: MATRICES; LINEAR ALGEBRAS